Peculiarities of the course and diagnostics of necrotizing entrocolitis in premature born cnildren - Yablon, O.; Rusak, N. (Journal of Education, Health and Sport, 2018)
Necrotizing enterocolitis (NEC) is an acute and potentially fatal disease characterized by inflammation and necrosis in the gastrointestinal tract (GIT). Due to the obscure multifactorial etiology, early diagnosis and effective treatment of NEC is limited. Consequently, effective strategies in the prevention of NEC are critically needed.The aim of the study: to establish clinical and diagnostic features of necrotizing enterocolitis of premature born children.Materials and methods: we examined 57 premature born children with necrotizing enterocolitis in Vinnytsya and Zhytomyr Regional Children's Clinical Hospital. The children were divided into three groups depending on the severity of the NEC: the first group consisted of 20 preterm infants infants with NEC І stage, the second group consisted of 30 preterm infants with NEC ІІ stage, the third group consisted of 7 preterm infants with NEC of the 3rd stage. The control group consisted of 10 preterm infants without NEC.The content of the protein that binds fatty acids (intestinal fatty acid binding proteins - I-FABP) in the blood serum was determined using the Human I-FABP (Hycult Biotech, Netherlands) assay, according to the manufacturer's instructions.The statistical processing of the obtained results was carried out using the software package Statistica 6.1. In order to determine the prognostic value of I-FABP in blood serum, we used the Receiver Operating Characteristic (ROC).Results: the analysis of the results of breast feeding allowed to establish that children from III and II groups started enteral nutrition later - by 3.6 ± 0.7 and 2.9 ± 0.4 days of life, than children of group ІІ - by 1.4 ± 0.1 days of life and children from the control group - by 1.2 ± 0.1 days of life (р <0.01). In the clinical picture of necrotizing enterocolitis, among the nonspecific symptoms, the symptoms of a "white spot", and bradycardia (p <0.05) were significantly more likely to occur, among abdominal manifestations - abdominal distension, weak peristalsis, contouring of the intestinal loops, moderate edema of the anterior abdominal wall (p <0.05). In all preterm infants with necrotizing enterocolitis, the content of the protein binding fatty acids (I-FABP) in serum has been elevated (p <0.05). The serum I-FABP value of ≥ 727.50 pg / ml allows to identify necrotizing enterocolitis in premature babies with a sensitivity of 73.6% and a specificity of 72.2%, obtained by ROC analysis, the area under the ROC curve (AUC) is 0.883 [95% CI 0.806-0.961], indicating a high diagnostic value of the model.